IITA stepwise mobile application showcase video - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2019)
Showcasing the stepwise mobile application prototype developed by IITA Uganda and Mango Tree which is to be tested in the field with IITA impact partner extension workers to inform the potential for scaling up the use of this extension support tool.